Analisis Penggunaan Teknologi Blockchain Dalam Pengelolaan Big data - Cindy Rayani Sinulingga; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
Blockchain technology is a promising solution for managing large amounts of data (big data) to ensure data security and transparency. Utilizing blockchain technology to manage big data can help optimize security, reduce operational costs, and support data analysis. In an increasingly complex digital era, blockchain technology can help mitigate the risks of identity theft, document forgery, and data manipulation. This research examines the implementation of blockchain technology in big data management, discusses the benefits and challenges of applying blockchain technology in big data management, and provides practical guidance for organizations looking to implement blockchain technology in big data management.